Metode Creat Sentence Dalam Meningkatkan Hafalan Mufradat Siswa MA al-Amiriyyah Banyuwangi - Nawawi, Mahbub; Nur Azizah, Rahma Nanda (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
Vocabulary learning activities are the main activities in achieving the goals of learning Arabic at school. Many MA Al-Amiriyyah students experience difficulties in understanding the meaning of reading texts and questions due to their lack of mastery of the mufradat vocabulary. So the focus of this research is how to improve students' memorization of mufradat through the application of the creat sentence method. The research method used is a qualitative approach. The results of this research are that the application of the creat sentence method in improving the ability to memorize mufradat in MA al-Amiriyyah students is said to be good, proven by memorizing vocabulary and students who are enthusiastic in participating in the learning process. Improving memorization of mufradat through the application of the creat sentence method has also been good and there are new variations in memorizing mufradat, as well as different ways of memorizing, among others.